1991
DOI: 10.1148/radiology.180.2.1648757
|View full text |Cite
|
Sign up to set email alerts
|

Nonpalpable breast lesions: stereotactic automated large-core biopsies.

Abstract: One hundred two patients with mammographically suspicious, nonpalpable lesions underwent stereotactic breast biopsy with a biopsy gun and an automated 14-gauge cutting needle. After biopsy, a localization wire was placed and surgical biopsy performed. There was agreement of the histologic results from the gun biopsy and the surgical biopsy specimens in 98 cases (96%), including 22 of 23 carcinomas (96%) (kappa = 0.936). The gun biopsy yielded findings that led to the correct diagnosis in two cases involving le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
4
9

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(146 citation statements)
references
References 0 publications
4
127
4
9
Order By: Relevance
“…This value may be overestimated due to the non-blindness of the pathologists (Irwig et al, 1994). In four studies large-core needle biopsy procedures as well as open biopsy procedures were performed on the same day (Parker et al, 1991;Elvecrog et al, 1993;Gisvold et al, 1994;Pijnappel et al, 1997). Therefore, pathologists may not have been blinded for the results of the reference standard test (open biopsy).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This value may be overestimated due to the non-blindness of the pathologists (Irwig et al, 1994). In four studies large-core needle biopsy procedures as well as open biopsy procedures were performed on the same day (Parker et al, 1991;Elvecrog et al, 1993;Gisvold et al, 1994;Pijnappel et al, 1997). Therefore, pathologists may not have been blinded for the results of the reference standard test (open biopsy).…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic biopsy was performed with the patient in prone position by using a 14-gauge needle and a long throw biopsy gun. In four studies all histological diagnoses of large-core needle biopsy specimens were confirmed by additional open biopsy and generally these two procedures took place on the same day (Parker et al, 1991;Elvecrog et al, 1993;Gisvold et al, 1994;Pijnappel et al, 1997). In the study of Jackman et al (1999), 295 patients (61%) with a benign diagnosis on large-core needle biopsy did not undergo immediate open biopsy, but mammographic follow-up.…”
Section: Meta-analysis Of Diagnostic Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Mammographically directed stereotaxic biopsy has become a recognized alternative to surgical biopsy for certain cases of breast cancer, with stereotaxic biopsy reliability now approaching that of surgical biopsy [30][31][32]. A variety of prototype stereotaxic devices have been built for MR-directed breast biopsy and needle localization [33][34][35][36][37][38].…”
Section: Stereotaxismentioning
confidence: 99%
“…Therefore, newer techniques and instruments, including stereotactic CT and ultrasound guidance are used for the diagnosis of small nonpalpable breast tumors. [14][15][16][17][18] Unfortunately, these technologies are usually not available in small clinics, require additional personnel, and as a result are less affordable. In this paper we present a technology and instrumentation based on low coherence interferometry for fine needle aspiration breast biopsy guidance.…”
Section: Introductionmentioning
confidence: 99%